2005
DOI: 10.1002/ana.20663
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels and the risk of Parkinson disease

Abstract: In a prospective population-based cohort study among 4,695 participants aged 55 years and older, with repeated in-person examination and on average 9.4 years of follow-up, we observed that higher serum levels of uric acid were associated with a significantly decreased risk of Parkinson disease (adjusted hazard ratio per standard deviation increase 0.71 [95% confidence interval 0.51-0.98]), with evidence for a dose-effect relationship (p value for trend over quartiles 0.040). Our findings support the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
188
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(205 citation statements)
references
References 19 publications
15
188
1
1
Order By: Relevance
“…The inverse association was stronger in non-smokers than smokers [659].The Rotterdam study also found lower PD risk with increasing baseline serum uric acid (p for trend 0.04), but no interaction by smoking status or gender [660]. Similarly, a case-control study nested within the Health Professionals Follow-up Study of men reported an inverse association between baseline serum uric acid and PD (RR 0.43, 95% CI 0.18-1.02 for highest versus lowest quartile of serum uric acid, p for trend 0.017) [661].…”
Section: Uric Acid and Goutmentioning
confidence: 77%
“…The inverse association was stronger in non-smokers than smokers [659].The Rotterdam study also found lower PD risk with increasing baseline serum uric acid (p for trend 0.04), but no interaction by smoking status or gender [660]. Similarly, a case-control study nested within the Health Professionals Follow-up Study of men reported an inverse association between baseline serum uric acid and PD (RR 0.43, 95% CI 0.18-1.02 for highest versus lowest quartile of serum uric acid, p for trend 0.017) [661].…”
Section: Uric Acid and Goutmentioning
confidence: 77%
“…Studies have evaluated a potential association between serum UA and the risk of developing Parkinson's disease, finding a lower risk among individuals with higher levels of serum UA. 31,32 Significant associations were detected between variations in SLC2A9 and memory performance. It was observed that higher UA levels might be associated with increased performance on memory-related tasks.…”
Section: Discussionmentioning
confidence: 97%
“…Based on a prospective population study, higher levels of serum UA were also associated with a decreased risk of PD (Chen, Mosley, Alonso, & Huang, 2009; de Lau, Koudstaal, Hofman, & Breteler, 2005). Low serum UA levels have been associated with an increased risk for developing PD, but it is unclear whether the UA levels are generally low among individuals who are prone to PD or whether the UA levels decrease during the long preclinical stages of PD (Annanmaki, Pohja, Parviainen, Hakkinen, & Murros, 2011).…”
Section: Discussionmentioning
confidence: 99%